Bifunctional catalyst for lignite / biomass hydro-liquefaction as well as preparation method and application of bifunctional catalyst
By regulating the crystal surface structure of copper-based catalysts and designing that Cu2+ and Cu+ coexist, combining CuO, Cu2O and NiO interactions, it forms a Cu/Ni@Cu2O composite material, solving the moisture barrier and catalyst efficiency in lignite/biomass hydrogenation liquefaction The problem of low efficiency of hydrogenation liquefaction conversion and catalytic effect is achieved.
Patent Information
- Application Number
- CN202411114413.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2024-12-17
AI Technical Summary
In the prior art, lignite or biomass is hindered by moisture during the liquefied hydrogenation process, resulting in insufficient supply of active hydrogen and poor hydrogenation matching, which limits the efficiency and economy of lignite/biomass hydrogenation liquefaction, and lacks high efficiency. The dual-function catalyst can catalyze the water-gas transformation reaction and the hydrogenation reaction simultaneously.
The low-temperature copper-based water-gas transformation reaction catalyst is used as the substrate. By regulating the Cu2O crystal surface structure and designing the coexistence of Cu2+ and Cu+, combining the strong metal-load interaction of CuO, Cu2O and NiO, it forms a Cu/Ni@Cu2O composite material as a dual function Catalysts to improve catalytic performance and hydrogenation effect.
It realizes efficient catalytic water-gas transformation reaction and hydrogenation reaction, improves the overall catalytic hydrogenation effect, improves the liquefaction conversion rate of lignite/biomass, and is simple in preparation, which is suitable for large-scale production.
Smart Images

Figure CN119140096A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogenation liquefaction, and in particular to a bifunctional catalyst for lignite / biomass hydrogenation liquefaction and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] With the increasing demand for petroleum-based liquid fuels and the reduction in available reserves of petroleum resources, methods for producing usable liquid fuels from solid fuels such as coal or biomass have attracted more and more attention.
[0004] Among coal resources, lignite with high water content accounts for more than half, and biomass fuel also contains a large amount of water. The water in lignite or biomass will hinder the mass transfer during liquefaction and hydrogenation. Therefore, lignite / biomass needs to be dried and pretreated before liquefaction and hydrogenation, which limits the conversion efficiency and economy of lignite.
[0005] The water-gas shift reaction (WGSR) can react the carbon in lignite or biomass with water and convert it in situ into an active hydrogen source (referred to as "active hydrogen"). Active hydrogen can be used as an auxiliary hydrogen source for the liquefaction of lignite or biomass, and can improve the effect of hydrogenation liquefaction while reducing the moisture in lignite or biomass. However, the key to limiting the large-scale application of this technology is the insufficient supply of active hydrogen and the poor matching of hydrogenation, so an efficient catalyst must be added. At present, the catalyst for the water-gas shift reaction is only aimed at catalyzing the active hydrogen generation reaction, and the catalytic activity needs to be improved. Therefore, the development of a highly active bifunctional catalyst that can be applied to both the water-gas shift reaction and the lignite / biomass hydrogenation reaction is crucial to strengthening the entire lignite / biomass hydrogenation liquefaction process. Summary of the invention
[0006] In order to overcome the above problems, the present invention provides a bifunctional catalyst for lignite / biomass hydrogenation liquefaction and its preparation method and application. The present invention uses a low-temperature copper-based water-gas shift reaction catalyst as a substrate, regulates the Cu2O crystal surface structure to increase the catalytic sites, and designs the Cu 2+ With Cu + Coexistence enhances the catalytic performance of water-gas shift reaction at low temperature. In addition, CuO, Cu2O and NiO form new contact interfaces and active sites under strong metal-support interaction (SMSI), effectively catalyzing water-gas shift reaction and hydrogenation reaction, achieving synergistic bifunctional catalysis and improving the overall catalytic hydrogenation effect.
[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0008] The first aspect of the present invention provides a method for preparing a bifunctional catalyst for lignite / biomass hydroliquefaction, comprising:
[0009] (1) Using a liquid phase precipitation method, divalent copper salt is used as a precursor, polyvinyl pyrrolidone (PVP) and alkali solution are added for precipitation, and then a reducing agent is added to obtain Cu2O powder;
[0010] (2) Using divalent nickel salt as a precursor, a precipitant is added to uniformly precipitate Ni(OH)2 on the surface of Cu2O powder. After calcination in an inert gas atmosphere, a Cu / Ni@Cu2O composite material is obtained, which is a bifunctional catalyst.
[0011] The second aspect of the present invention provides a bifunctional catalyst for lignite / biomass hydroliquefaction prepared by the above preparation method.
[0012] The third aspect of the present invention provides the use of the above-mentioned bifunctional catalyst for lignite / biomass hydroliquefaction in catalyzing lignite or biomass hydroliquefaction.
[0013] A fourth aspect of the present invention provides a method for hydroliquefaction, wherein lignite or biomass is contacted with a hydrogenation catalyst in a hydroliquefaction hydrogen supply solvent under hydrogenation reaction conditions, wherein the hydrogenation catalyst is the above-mentioned bifunctional catalyst for lignite / biomass hydroliquefaction.
[0014] The beneficial effects of the present invention are:
[0015] (1) In the present invention, polyvinyl pyrrolidone (PVP) is used as a surfactant to control the surface energy of low-energy crystals, thereby facilitating the precipitation of Cu2O crystals; a reducing agent is added to regulate the crystal surface to obtain Cu2O crystals. Ni(OH)2 is then loaded on the surface of the Cu2O crystals. When calcined in an inert gas atmosphere, Ni(OH)2 will lose water to obtain NiO, and the Cu2O without Ni(OH)2 loaded on the surface will be oxidized to CuO, and finally a Cu / Ni@Cu2O composite material composed of CuO, Cu2O and NiO is obtained, which is a bifunctional catalyst.
[0016] The present invention uses a low-temperature copper-based water-gas shift reaction catalyst as a substrate, adds a reducing agent to regulate the Cu2O crystal surface structure to increase the catalytic sites, and at the same time designs the Cu 2+ With Cu + Coexistence enhances the catalytic performance of water-gas shift reaction at low temperature. In addition, CuO, Cu2O and NiO form new contact interfaces and active sites under strong metal-support interaction (SMSI), effectively catalyzing water-gas shift reaction and liquefaction hydrogenation reaction, achieving synergistic bifunctional catalysis and improving the overall catalytic hydrogenation effect.
[0017] (2) The experimental results in the present invention show that the Cu / Ni@Cu2O composite material composed of CuO, Cu2O and NiO can efficiently catalyze the water-gas shift reaction and the liquefaction conversion rate of high-water-content lignite when used as a catalyst.
[0018] (3) The bifunctional catalyst for lignite / biomass hydrogenation liquefaction provided by the present invention has a simple and convenient synthesis method, high yield, and is easy to prepare, and is suitable for scale-up synthesis and actual production application. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0020] Figure 1 The present invention provides a preparation process of polyhedral Cu2O and Cu / Ni@Cu2O composite materials;
[0021] Figure 2 1 is a scanning electron microscope image of different Cu2O crystals in Examples 1 to 3; from left to right are scanning electron microscope images of different Cu2O crystals in Example 1, Example 2 and Example 3;
[0022] Figure 3 This is a scanning electron microscope image of the Cu / Ni@Cu2O composite material obtained in Example 1;
[0023] Figure 4 This is the EDS image of the Cu / Ni@Cu2O composite material obtained in Example 1. DETAILED DESCRIPTION
[0024] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0025] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0026] A first typical embodiment of the present invention provides a method for preparing a bifunctional catalyst for lignite / biomass hydroliquefaction, comprising:
[0027] (1) Using a liquid phase precipitation method, divalent copper salt is used as a precursor, polyvinyl pyrrolidone (PVP) and alkali solution are added for precipitation, and then a reducing agent is added to obtain Cu2O powder;
[0028] (2) Using divalent nickel salt as a precursor, a precipitant is added to uniformly precipitate Ni(OH)2 on the surface of Cu2O powder. After calcination in an inert gas atmosphere, a Cu / Ni@Cu2O composite material is obtained, which is a bifunctional catalyst.
[0029] In one or more embodiments, in step (1), the divalent copper salt includes copper sulfate.
[0030] In one or more embodiments, in step (1), the molar ratio of the divalent copper salt, polyvinyl pyrrolidone (PVP) and the alkali solution is 1:2.5-7.5:5-8, preferably 1:3.6:5-8.
[0031] In one or more embodiments, in step (1), the reducing agent comprises glucose (C6H 12 O6), vitamin C (C6H8O6) and hydroxylamine hydrochloride (H3NOHCl), preferably vitamin C (C6H8O6). Glucose (C6H 12 When C6H8O6 is used as a reducing agent, cubic Cu2O powder (C-Cu2O-(100)) can be obtained; when vitamin C (C6H8O6) is used as a reducing agent, octahedral Cu2O powder (O-Cu2O-(111)) can be obtained; when hydroxylamine hydrochloride (H3NOHCl) is used as a reducing agent, rhombic dodecahedron Cu2O powder (D-Cu2O-(110)) can be obtained.
[0032] In one or more embodiments, in step (1), the molar ratio of the divalent copper salt to the reducing agent is 1:2-5.
[0033] In one or more embodiments, in step (2), the divalent nickel salt includes nickel nitrate.
[0034] In one or more embodiments, the mass ratio of the divalent nickel salt in step (2) to the divalent copper salt in step (1) is 10% to 30%:1.
[0035] In one or more embodiments, in step (2), the precipitant comprises a sodium hydroxide solution.
[0036] In one or more embodiments, the calcination temperature is 350-450° C., and the calcination time is 2-4 hours, preferably calcination at 400° C. for 2 hours.
[0037] A second typical embodiment of the present invention provides a bifunctional catalyst for lignite / biomass hydroliquefaction prepared by the above preparation method.
[0038] A third typical embodiment of the present invention provides the use of the above-mentioned bifunctional catalyst for lignite / biomass hydroliquefaction in catalyzing lignite or biomass hydroliquefaction.
[0039] A fourth typical embodiment of the present invention provides a method for hydroliquefaction, wherein lignite or biomass is contacted with a hydrogenation catalyst in a hydrogen supply solvent for hydroliquefaction under hydrogenation reaction conditions, wherein the hydrogenation catalyst is the bifunctional catalyst for the above-mentioned lignite / biomass hydroliquefaction.
[0040] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0041] Figure 1 This is the preparation process of the polyhedral Cu2O and Cu / Ni@Cu2O composite materials in the present invention.
[0042] Example 1
[0043] refer to Figure 1 , dissolve 0.01mol CuSO4·5H2O in 100mL deionized water and stir ultrasonically for 10min. Add 4g polyvinylpyrrolidone (PVP) to the solution and stir for 15min. Transfer the mixed solution to a 500mL three-necked flask and heat it in a 55℃ water bath for 0.5h. Add 100mL 0.7mol / L NaOH solution dropwise (drop rate of 5-6s / drop) to the three-necked flask and let the reaction last for 1h. Subsequently, add 100mL 0.3mol / L reducing agent (C6H8O6) to the three-necked flask (drop rate of 5-6s / drop) and let the reaction last for 2h. The mixed solution after the reaction was sealed and aged for 6 hours, and the precipitated powder was collected and washed 6 times by centrifugation at 11000r / min with anhydrous ethanol solution (ultrapure water: anhydrous ethanol volume ratio is 1:1), and finally vacuum dried at 60℃ for 12 hours to obtain O-Cu2O-(111) powder. The scanning electron microscope image of O-Cu2O-(111) powder is shown in the figure. Figure 2 shown.
[0044] Dissolve 0.1g Ni(NO3)·6H2O (about 20%wt of the mass of Cu2O) in 100mL deionized water and disperse ultrasonically for 10min; add 0.5g of the above O-Cu2O-(111) powder and 0.1g antioxidant (ascorbic acid) to the nickel nitrate solution and stir for 15min. Add 100mL 0.1mol / L NaOH solution dropwise to the mixed solution (drop rate is 5-6s / drop), and after the dropwise addition is completed, stir and react for 1h. The reacted solution is sealed and allowed to stand for 5h, and the precipitated powder is collected and washed by centrifugation at 11000r / min for 6 times with anhydrous ethanol solution (ultrapure water: anhydrous ethanol volume ratio is 1:1), and finally dried in vacuum at 60℃ for 12h to obtain a powder containing Cu-Ni.
[0045] The powder containing Cu-Ni is placed in a tubular furnace, argon is introduced for 10 minutes, the heating rate is 2°C / min, and it is calcined at 400°C for 2 hours. After cooling to room temperature, it is taken out and ground to obtain a Cu / Ni@Cu2O composite material composed of CuO, Cu2O and NiO, which is a bifunctional catalyst.
[0046] The scanning electron microscope spectrum of the Cu / Ni@Cu2O composite material obtained in this example is as follows Figure 3 The elemental composition analysis of Cu / Ni@Cu2O composite materials is shown in Figure 4 As shown in the EDS figure.
[0047] Example 2
[0048] refer to Figure 1 , dissolve 0.01mol CuSO4·5H2O in 100mL deionized water and stir ultrasonically for 10min. Add 6g polyvinylpyrrolidone (PVP) to the solution and stir for 15min. Transfer the mixture to a 500mL three-necked flask and heat it in a 55℃ water bath for 0.5h. Add 100mL 0.5mol / L NaOH solution dropwise (drop rate 5-6s / drop) to the three-necked flask and let the reaction last for 1h. Then, add 100mL 0.2mol / L reducing agent (C6H 12 O6) was added (drip rate of 5-6s / drop) into a three-necked flask and the reaction was continued for 2h. The mixed solution was sealed and aged for 6h. The precipitated powder was collected and washed 6 times by centrifugation at 11000r / min with anhydrous ethanol solution (ultrapure water: anhydrous ethanol volume ratio of 1:1). Finally, it was vacuum dried at 60℃ for 12h to obtain C-Cu2O-(100) powder. The scanning electron microscope image of C-Cu2O-(100) powder is shown in the figure. Figure 2 shown.
[0049] Dissolve 0.1g Ni(NO3)·6H2O (about 20%wt of the mass of Cu2O) in 100mL deionized water and disperse ultrasonically for 10min; add 0.5g of the above C-Cu2O-(100) powder and 0.1g antioxidant (ascorbic acid) to the nickel nitrate solution and stir for 15min. Add 100mL 0.1mol / L NaOH solution dropwise to the mixed solution (drop rate is 5-6s / drop), and after the dropwise addition is completed, stir and react for 1h. The reacted solution is sealed and allowed to stand for 5h, and the precipitated powder is collected and washed by centrifugation at 11000r / min for 6 times with anhydrous ethanol solution (ultrapure water: anhydrous ethanol volume ratio is 1:1), and finally dried in vacuum at 60℃ for 12h to obtain a powder containing Cu-Ni.
[0050] The powder containing Cu-Ni is placed in a tubular furnace, argon is introduced for 10 minutes, the heating rate is 2°C / min, and it is calcined at 400°C for 2 hours. After cooling to room temperature, it is taken out and ground to obtain a Cu / Ni@Cu2O composite material composed of CuO, Cu2O and NiO, which is a bifunctional catalyst.
[0051] Example 3
[0052] Dissolve 0.01 mol CuSO4·5H2O in 100 mL deionized water and stir ultrasonically for 10 min. Add 6 g polyvinyl pyrrolidone (PVP) to the solution and stir for 15 min. Transfer the mixture to a 500 mL three-necked flask and heat it in a 55°C water bath for 0.5 h. Add 100 mL 0.7 mol / L NaOH solution dropwise (drop rate of 5-6 s / drop) to the three-necked flask and allow to react for 1 h. Subsequently, add 100 mL 0.5 mol / L reducing agent (H3NOHCl) to the three-necked flask (drop rate of 5-6 s / drop) and allow to react for 1 h. The mixed solution after the reaction was sealed and allowed to stand for 6 hours, and the precipitated powder was collected and washed 6 times by centrifugation at 11000r / min with anhydrous ethanol solution (ultrapure water: anhydrous ethanol volume ratio is 1:1), and finally vacuum dried at 60℃ for 12 hours to obtain D-Cu2O-(110) powder. The scanning electron microscope image of D-Cu2O-(110) powder is shown in the figure. Figure 2 shown.
[0053] Dissolve 0.1g Ni(NO3)·6H2O (about 20%wt of the mass of Cu2O) in 100mL deionized water and disperse ultrasonically for 10min; add 0.5g of the above D-Cu2O-(110) powder and 0.1g antioxidant (ascorbic acid) to the nickel nitrate solution and stir for 15min. Add 100mL 0.1mol / L NaOH solution dropwise to the mixed solution (drop rate is 5-6s / drop), and after the dropwise addition is completed, stir and react for 1h. The reacted solution is sealed and allowed to stand for 5h, and the precipitated powder is collected and washed by centrifugation at 11000r / min for 6 times with anhydrous ethanol solution (ultrapure water: anhydrous ethanol volume ratio is 1:1), and finally dried in vacuum at 60℃ for 12h to obtain a powder containing Cu-Ni.
[0054] The powder containing Cu-Ni is placed in a tubular furnace, argon is introduced for 10 minutes, the heating rate is 2°C / min, and it is calcined at 400°C for 2 hours. After cooling to room temperature, it is taken out and ground to obtain a Cu / Ni@Cu2O composite material composed of CuO, Cu2O and NiO, which is a bifunctional catalyst.
[0055] Comparative Example 1
[0056] Dissolve 0.01 mol CuSO4·5H2O in 100 mL deionized water and stir ultrasonically for 10 min. Add 4 g polyvinyl pyrrolidone (PVP) to the solution and stir for 15 min. Transfer the mixture to a 500 mL three-necked flask and heat in a 55°C water bath for 0.5 h. Add 100 mL 0.7 mol / L NaOH solution dropwise (drop rate of 5-6 s / drop) to the three-necked flask and allow to react for 1 h. Subsequently, add 100 mL 0.3 mol / L reducing agent (C6H8O6) to the three-necked flask (drop rate of 5-6 s / drop) and allow to react for 2 h. The mixed solution after the reaction was sealed and aged for 6 hours, and the precipitated powder was collected and washed six times by centrifugation at 11000r / min with anhydrous ethanol solution (ultrapure water: anhydrous ethanol volume ratio is 1:1), and finally vacuum dried at 60°C for 12 hours to obtain O-Cu2O-(111) powder.
[0057] Comparative Example 2
[0058] Dissolve 0.01 mol CuSO4·5H2O in 100 mL deionized water and stir ultrasonically for 10 min. Add 6 g polyvinyl pyrrolidone (PVP) to the solution and stir for 15 min. Transfer the mixture to a 500 mL three-necked flask and heat in a 55°C water bath for 0.5 h. Add 100 mL 0.5 mol / L NaOH solution dropwise (drop rate 5-6 s / drop) to the three-necked flask and allow to react for 1 h. Subsequently, add 100 mL 0.2 mol / L reducing agent (C6H12 O6) was added (dropping rate of 5-6s / drop) into a three-necked flask, and the reaction was continued for 2h. The mixed solution was sealed and aged for 6h, and the precipitated powder was collected and washed by centrifugation at 11000r / min for 6 times with anhydrous ethanol solution (ultrapure water: anhydrous ethanol volume ratio of 1:1), and finally vacuum dried at 60℃ for 12h to obtain C-Cu2O-(100) powder.
[0059] Comparative Example 3
[0060] Dissolve 0.01 mol CuSO4·5H2O in 100 mL deionized water and stir ultrasonically for 10 min. Add 6 g polyvinyl pyrrolidone (PVP) to the solution and stir for 15 min. Transfer the mixture to a 500 mL three-necked flask and heat it in a 55°C water bath for 0.5 h. Add 100 mL 0.7 mol / L NaOH solution dropwise (drop rate of 5-6 s / drop) to the three-necked flask and allow to react for 1 h. Subsequently, add 100 mL 0.5 mol / L reducing agent (H3NOHCl) to the three-necked flask (drop rate of 5-6 s / drop) and allow to react for 1 h. The mixed solution after the reaction was sealed and aged for 6 hours, and the precipitated powder was collected and washed 6 times by centrifugation at 11000r / min with anhydrous ethanol solution (ultrapure water: anhydrous ethanol volume ratio is 1:1), and finally vacuum dried at 60°C for 12 hours to obtain D-Cu2O-(110) powder.
[0061] Comparative Example 4
[0062] Dissolve 0.01 mol CuSO4·5H2O in 100 mL deionized water and stir ultrasonically for 10 min. Add 4 g polyvinyl pyrrolidone (PVP) to the solution and stir for 15 min. Transfer the mixture to a 500 mL three-necked flask and heat in a 55°C water bath for 0.5 h. Add 100 mL 0.7 mol / L NaOH solution dropwise (drop rate of 5-6 s / drop) to the three-necked flask and allow to react for 1 h. Subsequently, add 100 mL 0.3 mol / L reducing agent (C6H8O6) to the three-necked flask (drop rate of 5-6 s / drop) and allow to react for 2 h. The mixed solution after the reaction was sealed and aged for 6 hours, and the precipitated powder was collected and washed six times by centrifugation at 11000r / min with anhydrous ethanol solution (ultrapure water: anhydrous ethanol volume ratio is 1:1), and finally vacuum dried at 60°C for 12 hours to obtain O-Cu2O-(111) powder.
[0063] 0.1 g O-Cu2O-(111) powder was placed in a tube furnace, argon was introduced for 10 min, the heating rate was 2 °C / min, annealed at 400 °C for 2 h, cooled to room temperature, and then ground to obtain Cu x O Powder material.
[0064] Experimental Example 1
[0065] The catalysts prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were used to conduct CO conversion experiments. The specific process includes:
[0066] The water-gas shift reaction experiments were all carried out in a 60 mL stirred high temperature and high pressure reactor. The specific operation steps are as follows:
[0067] (1) Accurately weigh 5 g of water and catalyst (accounting for 1 wt.% of the reactants), add them into the reaction kettle, and seal the kettle.
[0068] (2) The reactor was repeatedly filled with high-purity nitrogen and then emptied. This operation was repeated three times. After the air in the reactor was replaced, the reaction gas was filled and then emptied. After this operation was repeated three times, CO was used as the reaction gas and filled to 4.0 MPa to ensure the purity of the reaction atmosphere.
[0069] (3) Set a temperature program, heat the reactor to 200°C at a heating rate of 10°C / min, stir the reactants in the reactor at a constant speed of 300 rpm, and maintain the reaction time for 2 h.
[0070] (4) After the reaction, the reactor was quickly cooled to room temperature with an ice-water mixture, the temperature and pressure were recorded, and the gas after the reaction was collected using an aluminum foil gas sampling bag. The CO, CO2 and H2 contents were analyzed using a gas chromatograph to calculate the CO conversion rate; CO conversion rate = (CO content before reaction - CO content after reaction) / CO content before reaction. The results are shown in Table 1.
[0071] Table 1 Effect of bifunctional catalyst on water-gas shift reaction (with CO conversion rate as evaluation index, %)
[0072] Example CO conversion Comparative Example CO conversion Example 1 85.23 Comparative Example 1 34.56 Example 2 77.33 Comparative Example 2 23.44 Example 3 80.45 Comparative Example 3 40.03 Comparative Example 4 64.28
[0073] As shown in Table 1, the catalytic efficiency of the catalysts in Examples 1, 2, and 3 is much higher than that in the comparative example, indicating the catalytic effect of Ni in the present invention; and Example 1 is higher than Examples 2 and 3, indicating the superiority of the octahedral Cu / Ni@Cu2O composite material; Comparative Example 4 is higher than Comparative Example 1, indicating that the Cu 2+ , Cu + Cu x O has higher catalytic properties than single Cu2O.
[0074] Experimental Example 2
[0075] The catalysts prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were used for hydrogenation liquefaction. Specific steps of lignite hydrogenation liquefaction:
[0076] The lignite hydroconversion test was carried out in a 150mL high temperature and high pressure automatic magnetic stirring reactor. The test operation process is as follows:
[0077] (1) Weigh 10 g of lignite, 3 g of deionized water (water is 30% of the weight of lignite), 30 g of tetralin (the weight of tetralin is 3 times that of lignite), and a catalyst (the weight of the catalyst is 2.5 wt.% of that of lignite), put them into a reaction kettle and seal it.
[0078] (2) Fill the kettle with 6.0MPa nitrogen, verify that the airtightness is good, then fill the kettle with about 6.0MPa nitrogen and exhaust it, repeat 3 times to exhaust the air in the kettle. Fill the kettle with synthesis gas (30% CO + 70% H2) to 4.0MPa and exhaust it, repeat 2 times, then fill the kettle with synthesis gas to 4.0MPa.
[0079] (3) Set the temperature control program to start heating to 420°C and set the speed of the electromagnetic stirrer to 500 rpm / min to ensure the uniformity of the raw materials, solvent and catalyst during the reaction.
[0080] (4) After the reaction is completed, the reactor is quickly cooled to room temperature with an ice-water mixture, the temperature and pressure at this time are recorded, and the agitator, cooling water and reaction controller are turned off. An aluminum foil gas sampling bag is used to collect the gas after the reaction, and THF is used as a solvent to collect the solid-liquid mixture in the reactor.
[0081] (5) The water content of the liquid-solid mixture is measured, and then heated and Soxhlet extraction is performed using n-hexane, toluene, and tetrahydrofuran, respectively. The component soluble in n-hexane is oil, the component soluble in toluene but insoluble in n-hexane is asphaltene, the component soluble in tetrahydrofuran but insoluble in toluene is pre-asphaltene, and the component insoluble in tetrahydrofuran is liquefied residue.
[0082] The results are shown in Table 2.
[0083] Table 2 Effect of bifunctional catalyst on catalytic hydrogenation of lignite (with conversion rate and product yield as evaluation indicators, %)
[0084]
[0085]
[0086] The catalytic effects of different catalysts can be clearly seen from the lignite hydrogenation liquefaction conversion rate, Example 1> Example 3> Example 2, indicating that this is less related to the catalyst components and is related to the catalyst crystal surface structure. The octahedral catalyst has a better catalytic hydrogenation effect; similarly, Examples 1, 2, and 3 are much greater than Comparative Examples 1, 2, and 3, indicating that the addition of the Ni component forms a hydrogenation-promoting catalytic effect; Comparative Example 4 is greater than Comparative Example 1, which also shows that the presence of Cu 2+ , Cu + Cux O has higher catalytic properties than single Cu2O. The lignite hydrogenation conversion rate has the same trend as oil, gas and water, and asphaltene and pre-asphaltene have little change, indicating that the catalyst mainly promotes the conversion of lignite hydrogenation to small molecular compounds. This hydrogenation conversion trend is also consistent with the conversion rate of CO in the water-gas shift reaction in Table 1, indicating that the catalyst effectively promotes the water-gas shift reaction and lignite hydrogenation liquefaction reaction.
[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a bifunctional catalyst for lignite / biomass hydrogenation liquefaction, characterized in that: include: (1) Using a liquid phase precipitation method, divalent copper salt is used as a precursor, polyvinyl pyrrolidone and alkali solution are added for precipitation, and then a reducing agent is added to obtain Cu2O powder; (2) Using divalent nickel salt as a precursor, a precipitant is added to uniformly precipitate Ni(OH)2 on the surface of Cu2O powder. After calcination in an inert gas atmosphere, a Cu / Ni@Cu2O composite material is obtained, which is a bifunctional catalyst for lignite / biomass hydrogenation liquefaction.
2. The preparation method according to claim 1, characterized in that The divalent copper salt includes copper sulfate.
3. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of the divalent copper salt, polyvinyl pyrrolidone and alkali solution is 1:2.5-7.5:5-8, preferably 1:3.6:5-8.
4. The preparation method according to claim 1, characterized in that: In step (1), the reducing agent includes glucose, vitamin C and hydroxylamine hydrochloride, preferably vitamin C; Or, the molar ratio of the divalent copper salt to the reducing agent is 1:2-5.
5. The preparation method according to claim 1, characterized in that: In step (2), the divalent nickel salt includes nickel nitrate.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the divalent nickel salt in step (2) to the divalent copper salt in step (1) is 10% to 30%:1; Alternatively, the precipitating agent comprises sodium hydroxide solution.
7. The preparation method according to claim 1, characterized in that: The calcination temperature is 350-450°C, and the calcination time is 2-4 hours, preferably calcination at 400°C for 2 hours.
8. A bifunctional catalyst for lignite / biomass hydrogenation liquefaction prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the bifunctional catalyst for lignite / biomass hydroliquefaction according to claim 8 in catalyzing lignite or biomass hydroliquefaction.
10. A method for hydrogenation liquefaction, characterized in that: Under hydrogenation reaction conditions, lignite or biomass is contacted with a hydrogenation catalyst in a hydrogenation liquefaction hydrogen supply solvent, wherein the hydrogenation catalyst is the bifunctional catalyst for lignite / biomass hydrogenation liquefaction as claimed in claim 8.
